The Impact of Upin and Ipin Animation on Aggressive Behavior in Children Aged 5–6 Years: A Quantitative Experimental Study - Utari, Sindy Mey Dwi; Nur Hidayah; Pramono (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
The study aimed to investigate the impact of the Upin Ipin animated film on the aggressive behavior of 5-6-year-old children at TK Dharma Wanita I Blitaran. This research employed a pretest-posttest control group design, and data were collected through observation sheets and documentation. Data analysis was conducted using SPSS 24. The study revealed that the Upin Ipin animated film significantly influenced children's aggressive behavior. The research findings indicated that the experimental group experienced increased aggressive behavior. The average pretest score was 6.60, while the average posttest score was 7.90. The results of the hypothesis test using paired sample t-test showed a significant value of 0.000 < 0.05, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative view (Ha). The experimental group exhibited increased aggressive behavior after watching the film, as evidenced by the higher average posttest scores than the pretest scores. However, this study also acknowledges its limitations in scope, as it focused solely on 5-6-year-old children and the influence of a specific animated film. The research emphasizes the importance of parental guidance in children's media consumption. While animated films like Upin Ipin can potentially influence aggressive behavior, they can also serve as practical educational tools to promote positive social behavior and other essential skills, depending on their content and presentation. The novelty of this research lies in its focus on the influence of a specific animated film, Upin Ipin, on children's aggressive behavior.